Geldpolitik und Zinsbildung unter besonderer Berücksichtingung der Gegenwärtigen Situation - Hennies, Manfred O.E. (Estonian Discussions on Economic Policy, 2017)
At present the ECB is striving, through its so-called zero interest rate policy, to avoid deflationary developments because, as past experience shows, a further price decay would be expected to lead to bankruptcies and be a strain on the real economy. Complementary quantitative easing (QE) and the resulting drop in returns on bought up securities will hopefully lead to the commercial banks giving more credits to small and medium-sized enterprises which are unable to, or have difficulty in financing themselves through bonds. Reducing the margin between interest income and refinancing costs to the lowest level possible has caused serious problems for credit institutions. The same applies, due to the reduced interest rates on loans, to the insurance companies and pension funds, which tend to invest conservatively. — Zero interest rate policy, which in itself is a contradiction of the principles of a market economy, should be relinquished as soon as possible. A return to a monetary policy which does not lead to misallocation and structural distortions is urgently necessary.